APPLICATION OF ARTIFICIAL INTELLIGENCE IN DISTRIBUTION OF UNIVERSITY SYSTEM MODEL - Mai, Nguyen Hoang (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Higher education and improving the quality indicators of higher education is always a hot problem for all time. Education is the core of the country's society. Over hundreds of years, higher education systems have changed to match the level of civilization, the amount of human knowledge, the new pace of life and the development of information technology. . Many higher education methods in developed countries have applied very effectively and met many high educational standards such as ABET, QS - Quacquarelli Symonds, Times Higher Education, SARWU - Shanghai Academic Ranking of World Universities ... Using AI, Big Data has also been applied to minimize time dependence and increase human understanding. From the traditional education model, the world has come to teach online with the application of IoT. In this article, we introduce a new model of higher education that can be applied in the near future to higher-end IoT applications than online, distributed education. We call this the Distributed Higher Education System Model – DUSM. With application of artificial intelligence to make virtual environment in education, we hope have a big change in education to advance quality of education. The analysis of the method will be presented in detail and hopefully it will be quickly applied to suit the capacity of social information technology.